(untitled) (Balneo and PRM Research Journal, 2024)
Lumbar disc herniation is a degenerative neurological disorder characterized by a notable rise in incidence and prevalence among the population in modern times. It is primarily caused by factors such as microtrauma, sedentary lifestyle, prolonged static postures, excessive time spent at the computer, and overexertion. Materials and methods: A study was conducted retrospectively from 2022 to 2023 on patients who were admitted with lumbar disc herniation, at the Neurosurgery Hospital "Prof. N. Oblu”, in Iași.The research focused on showcasing the aspects of disc issues/pathology in the North Eastern re-gion.Findings; The research included 1969 individuals with a majority noted among par-ticipants, from rural areas and females.The majority of patients fell into the adult age range of 41 60 years. Surgical procedures were performed on 71% of the patients while conservative treatment was administered to the remaining 29%.The distribution of ages shows that most individuals undergoing surgery or receiving conservative treatment fall, within the adult age range of 41 to 60 years. Surgery is performed on 71% of patients while conservative treatment is given in 29% of cases.All patients were advised to undergo follow up remedial therapy upon discharge. We faced challenges in evaluating the level of adherence which posed a limitation in our study.Conclusions: The study brings to the forefront the need for reparative therapy for patient’s socio-professional and family reinte-gration and improvement of quality of life.